The impacts of international, national and institutional conditions for higher education on the primary processes of teaching and learning in the higher education institutions in Vietnam / Trinh Truong - Truong, Trinh (Research Management Institute (RMI), 2010)
This paper describes how the international, national and institutional conditions affect the primary processes of teaching and learning in the Vietnamese higher education institutions. Under such influences, the Vietnamese higher education institutions are facing both challenges and opportunities in terms of the competitions among institutions. establishment of credit-based system, quality assurance and accreditation.